The «second hand» of the anthologist between canons and textbooks (Configurazioni. Research on contemporary poetry, 2023)
Portrayed as «the literary genre of the 20th-century» (Macrì 1968), the literary anthology, both canonical and scholastic, can be approached from a multi-perspective view. First of all, the anthology shows up as a second-degree recompilation of texts drawn from first-composed works, poetry collections in this case. In this meaning are intended the excerpts taken from the compiler’s «seconde main» (Compagnon 1979), who then set them up in his own arrangement, depending on his aesthetic ideas and criteria of historicisation. Beyond serving as an underlying instrument of literary canonisation, during the 20th-century the anthology has also served as the elective genre of school teaching, as a textbook.
Keywords: Poetry Anthologies; Italian Literature; Literary Canon; Twentieth-century Literary Histories; School Textbooks